Relationship between point-of-care ultrasound venous congestion assessment parameters, intravenous pressure, and venous return: a post-hoc analysis of a prospective cohort study - Ruste, Martin; Delas, Quentin; Reskot, Rehane; Fellahi, Jean-Luc; Jacquet-Lagrèze, Matthias (The Ultrasound Journal, 2025)
Background: A recent study suggested that point-of-care ultrasound (POCUS) venous congestion assessment poorly describes the changes in venous return during a fluid challenge. The aim of the present study was to explore the relationship between POCUS venous congestion assessment parameters and the determinants of venous return in steady state and during a fluid challenge.Methods: This study is a post-hoc analysis of a single-centre prospective cohort study of patients presenting acute circulatory failure and venous congestion. The protocol consisted in a fluid administration of 4mL/kg over five minutes, just preceded and followed by the acquisition of haemodynamic data and POCUS venous congestion assessment parameters (VExUS score and portal pulsatility index, PPi). Venous return (dVR) was defined as the difference between mean systemic filling pressure analogue estimated by the mathematical approach of Parkin and Leaning (Pmsa) and central venous pressure (CVP). Relationships between Pmsa, CVP, dVR, and VExUS score and PPi were analysed using linear regression and Jonckheere-Terpstra test for trend.Results: Thirty-two patients were included in the analysis. Fluid challenge induced a significant increase in CVP, Pmsa, dVR, and VExUS score. In steady state, there was a significant association of VExUS score and PPi with CVP (P-value = 0.006 and 0.002, respectively) and Pmsa (P-value = 0.004 and 0.003, respectively) but not with dVR (P-value = 0.943 and 0.408, respectively). The variations induced by fluid challenge in CVP, Pmsa and dVR were not associated with variations in PPi (P-value = 0.844, 0.912 and 0.716, respectively). Patients without VExUS score increase during the fluid challenge presented a higher increase in Pmsa than patients with an increase in VExUS score.Conclusion: In steady state, POCUS venous congestion assessment parameters are associated with CVP and Pmsa but not with dVR. After fluid administration, changes in POCUS venous congestion assessment parameters were not associated with changes in CVP, Pmsa, and dVR.